Public attitudes towards the implementation of pharmaceutical care services in community pharmacies – a 2025 nationwide cross-sectional survey among adults in Poland - Wrześniewska-Wal, Iwona; Sękowski, Kuba; Silczuk, Andrzej; Jankowski, Mateusz; Grudziąż-Sękowska, Justyna (Frontiers in Pharmacology, 2025)
IntroductionPharmacists, as healthcare professionals, can improve treatment outcomes by providing pharmaceutical care services and implementing adherence-supporting tools. In Poland, these services are still at an early stage of development, and data on public attitudes toward them remain limited.MethodsA nationwide cross-sectional survey was conducted using the computer-assisted web interviews (CAWI) method on a stratified sample of 1,102 adults, representative in terms of gender, age, and place of residence. A validated questionnaire was used to assess attitudes toward pharmaceutical care services and adherence-supporting interventions. Sociodemographic and health-related factors were analyzed using multivariable logistic regression.ResultsAttitudes toward pharmaceutical care were positive. The most frequently accepted services included drug interaction review (85.5%), explanation of dosing for new medications (83.5%), and monitoring therapy with previously unused medications (69.4%). Among adherence-supporting tools, instruction labels (85.5%) and simplified leaflets with pictograms (80.7%) were rated highest, followed by SMS or email reminders (59.2%) and additional pharmacist contact (46.7%–53.7%). Significant sociodemographic differences emerged: men more often valued shortened leaflets (83.1% vs. 77.8%), instruction labels (87.6% vs. 83.0%), and pharmacist follow-up (46.9% vs. 40.3%); respondents ≥60 years favored leaflets (85.2%) and labels (89.2%); parents more frequently accepted labels (87.8% vs. 81.6%). Higher education and better economic status were linked to more positive views of pharmaceutical care. Participants with chronic diseases more frequently accepted dosing explanations (86.1% vs. 80.4%), monitoring of new drugs (72.1% vs. 66.1%), and interaction reviews (88.1% vs. 82.2%), with diabetes or prediabetes emerging as the strongest predictor of positive attitudes. In multivariable analysis, male gender (aOR = 1.40; 95% CI = 1.10–1.79; p = 0.007) and good (aOR = 1.52; 95% CI = 1.04–2.21; p = 0.03) or average economic status (aOR = 1.64; 95% CI = 1.11–2.41; p = 0.01) were significantly associated with interest in free pharmacist consultations. Having children (aOR = 1.60; 95% CI = 1.15–2.23; p = 0.005) and occupational activity (aOR = 1.37; 95% CI = 1.03–1.81; p = 0.03) increased the likelihood of believing that a pharmacist consultation after receiving a prescription facilitates correct medication use.ConclusionImplementing pharmacist consultations alongside simple adherence tools may significantly improve medication safety and treatment effectiveness in patients with chronic conditions.